Monitoring law enforcement and illegal activities in the northern sector of the Parc National des Virunga, Democratic Republic of Congo - Mubalama, Leonard; Mushenzi, Norbert (Pachyderm, 2004)
This paper focuses on a year long (July 2002-July 2003) law-enforcement monitoring project in the northern sector of Parc National des Virunga (PNVi), which 'made a preliminary study of the background affecting elephant poaching and other illegal activities by using a state-of-the-art geographic information system (GIS)'. With recent data suggesting 'that is it not deforestation but defaunation that poses the greatest immediate threat to animal conservation' this study assessed the utility of both the conventional deterrence involving routine foot patrols within the study area associated with boundary checks and visits to neighbouring villages, as well as investigation operations following up information supplied through a network of informants outside the area. It appears that when effectively implemented these two operations are equally important in deterring wildlife offenders. The authors note 'that increased effectiveness in anti-poaching can be achieved only by appropriate law enforcement as a deterrent by providing information that site managers can use to determine how to allocate resources optimally to improve protection and management of elephants and other wildlife'. Although this study was carried out in an area that continues to suffer the consequences of a lengthy civil war this study suggests conservation measures based on deterrence can be implemented under precarious political conditions. Mubalama presented this article as the paper 'Monitoring of law enforcement and illegal activity in the northern sector of the Parc National des Virunga under siege with a focus on elephant (Loxodonta africana) poaching' during the 6th AFESG Meeting at Mokuti Lodge, Namibia, Dec 4-8, 2003.